1942
DOI: 10.1111/j.1365-2621.1942.tb17662.x
|View full text |Cite
|
Sign up to set email alerts
|

DIGESTION OF BEEF BY PAPAIN1

Abstract: The plant proteinase, papain, has found considerable application as a meat tenderizer but its use for this purpose has been largely empirical. The digestion of whole beef muscle and the survival of papain heated with whole muscle have not been studied quantitatively.The procedure usually recommended for tenderizing meat with papain is to paint the meat with a solution of the enzyme, then cook it after an interval of a few minutes. To be of use, the enzyme action must be rapid. Obviously, the proteolytic action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1963
1963
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Gottschall and Kies (1942) made an early attempt to study some of the modes of proteolytic enzyme action as possible tenderizers of beef. Correlations between morphological and panel observations have been conducted with particular reference to freeze-dehydrated meats, especially beef and pork.…”
mentioning
confidence: 99%
“…Gottschall and Kies (1942) made an early attempt to study some of the modes of proteolytic enzyme action as possible tenderizers of beef. Correlations between morphological and panel observations have been conducted with particular reference to freeze-dehydrated meats, especially beef and pork.…”
mentioning
confidence: 99%
“…Both ficin (Whitaker, 1957b) and bromelain (Murachi and Neurath, 1960) have been shown to be activated by sulfhydryl compounds. Gottschall and Kies (1942) showed that beef contained enough sulfhydryl groups to activate completely the papain used in their studies. Fig.…”
Section: And Discussionmentioning
confidence: 98%
“…Previous workers have shown that a number of proteolytic enzymes can solubilize the proteins of beef muscle and that there is a certain degree of selectivity among these enzymes in solubilizing the different protein fractions (Gottschall and Kies, 1942;Tappel Ef al., 19.56;Wang et al, 195s). Ficin, bromelain, and papain, all from tropical plants, and trypsin, from the pancreas, possess collagenase and elastase activities.…”
mentioning
confidence: 99%
“…The usually recommended procedure for tenderizing meat is to paint the meat with a solution of papain and then cook it after an interval of a few minutes (Gottschall and Kies, 1942;Hwang and Ivy, 1951). When the meat was painted with a solution of papain and then cooked, it was found that papain would not penetrate very far in the meat under such conditions, and the papain on the surface would be inactivated by heat before much digestion could take place (Hwang and Ivy, 1951;Gottschall and Kies, 1942).…”
Section: Methods Of Applicationmentioning
confidence: 99%
“…When the meat was painted with a solution of papain and then cooked, it was found that papain would not penetrate very far in the meat under such conditions, and the papain on the surface would be inactivated by heat before much digestion could take place (Hwang and Ivy, 1951;Gottschall and Kies, 1942).…”
Section: Methods Of Applicationmentioning
confidence: 99%